Proses Kegiatan Penghimpunan Dan Distribusi Wakaf Tunai Di Baitul Maal Hidayatullah Surabaya - Muhammad Afdhal; Siti Inayatul Faizah (Jurnal Ekonomi Syariah Teori dan Terapan, 2016)
This research adopts a qualitative approach with case study methodology. Data collection is done through carrying out interview with informants such as branch manager, financial manager, marketing staffs and several donators of Baitul Maal Hidayatullah. Secondary data comes under the form of documents pertaining to the practice performed by Baitul Maal Hidayatullah. The pattern matching technique is then used to compare patterns based on empirics with the predicted patterns. Cash waqf funds are collected through direct and indirect means. The collection of cash waqf funds by Baitul Maal Hidayatullah are in accordance with the procedures set out by Badan Wakaf Indonesia which are, analysis of needs, waqif profile identification, the product of waqf, and the transactional cost. The distribution of cash waqf funds by Baitul Maal Hidayatullah are in accordance with what has been ordained by the Direktorat Pemberdayaan Wakaf, which includes, waqf distribution for education and social services.